Analisis bibliometrik tentang perkembangan keamanan informasi dalam konteks tata kelola IT di pemerintahan - Kholifah, Briyana Qusnul; Zaman, Syahiduz (Maliki Interdisciplinary Journal, 2024)
In the rapidly evolving digital era, information security has become a critical aspect of IT governance in government. This study aims to map the development and research trends related to information security within the context of IT governance in government through a bibliometric analysis. Data were collected using Publish or Perish with Google Scholar, employing the keyword "IT Governance" and covering the years 2010-2024. The analysis was conducted using VOSviewer for visualization. The results indicate two main clusters in this research area: e-government and information security management. The overlay and density visualizations highlight the most prominent research areas and their intensity. Trend analysis shows an increased focus on information security, the implementation of AI and IoT, and the role of leadership in IT governance. This study contributes to academia by identifying future research directions, to practitioners by understanding trends and best practices, and to policysmakers by developing effective policies. Using bibliometric analysis and visualization tools, this research reveals patterns, trends, and gaps in the literature, providing valuable contributions to the development of knowledge and practice in IT governance and information security in government.